Nitrilases NIT1/2/3 Positively Regulate Flowering by Inhibiting MAF4 Expression in Arabidopsis - Yang, Shuang; Zhang, Tianqi; Wang, Ze; Zhao, Xiaofei; Li, Rui; Li, Jing (Frontiers in Plant Science, 2022)
NIT1, NIT2 and NIT3 are nitrilases ubiquitously existing in plant kingdom, which catalyze indole-3-acetonitrile into the most important auxin indole-3-acetic acid (IAA). Auxin is an indispensable hormone, which plays important roles in almost all processes of plant growth and development. However, there are few reports on the regulation of flowering time mediated by auxin. Here, we found that in Arabidopsis, nit1/2/3 showed a late flowering phenotype in short days. To explore the molecular mechanism by which NIT1/2/3 regulate flowering time, we performed transcriptome sequencing of nit1/2/3. The results showed that the expression of a MADS-box transcription factor gene MADS AFFECTING FLOWERING4 (MAF4) was dramatically increased in nit1/2/3 comparing to wild type. MAF4 is one of the paralogs of the potent flowering inhibitor FLOWERING LOCUS C (FLC). There are four other paralogs in FLC clade in Arabidopsis, including FLOWERING LOCUS M (FLM/MAF1), MAF2, MAF3 and MAF5. The late flowering phenotype of nit1/2/3 could not be observed in the maf4 background, indicating that the phenotype was specifically dependent on MAF4 rather than other FLC clade members. Interestingly, the expression of a lncRNA gene MAS, which is transcribed in the opposite direction of MAF4, was found significantly increased in nit1/2/3. MAS has been reported to activate MAF4 transcription by promoting histone 3 lysine 4 trimethylation (H3K4me3). As expected, H3K4me3 deposition at MAF4 locus in nit1/2/3 was highly enriched and significantly higher than that of wild type. In summary, we show that nitrilases NIT1/2/3 positively regulate flowering by repressing MAF4 through manipulating H3K4me3 modification. Further study needs to be performed to explore the largely unknown mechanisms behind it.